Evaluating individual training adaptation with smartphone-derived heart rate variability in a collegiate female soccer team - Flatt, A. A.; Esco, M. R. (The Journal of Strength and Conditioning Research, 2016)
Monitoring individual responses throughout training may provide insight to coaches regarding how athletes are coping to the current program. It is unclear if the evolution of heart rate variability (HRV) throughout training in team-sport athletes can be useful in providing early indications of individual adaptation. This study evaluated relationships between changes in resting cardiac autonomic markers derived from a novel smartphone device within the first 3 weeks of a 5-week conditioning program and the eventual change in intermittent running performance at week 5 among 12 collegiate female soccer players. Change variables from weeks 1 to 3 of the weekly mean and weekly coefficient of variation for resting heart rate (dRHRmean and dRHRcv, respectively) and log-transformed root mean square of successive R-R intervals multiplied by 20 (dLn rMSSDmean and dLn rMSSDcv, respectively) were compared with changes in Yo-Yo Intermittent Recovery Test Level 1 performance (dYo-Yo). A very large and significant correlation was found between dYo-Yo and dLn rMSSDcv (r = -0.74; p = <0.01) and a large nonsignificant correlation was found with dLn rMSSDmean (r = 0.50; p = 0.096). This study suggests that a decrease in Ln rMSSDcv within the first 3 weeks of training is a favorable response, indicative of positive adaptation. Collecting daily HRV data with a smartphone application using ultrashort HRV measures seems useful for athlete monitoring.